Detection of Aflatoxins and Fungal Contaminants in Packaged and Unpackaged Powdered Milk from Selected Vendors in Katsina Metropolis - Bishir, Sadiq; Yusuf, Abdulhamid; Lawal, Umar (International Journal of Bio-resource and Stress Management, 2026)
The experiment was conducted between June and September 2021 at the Biology Laboratory of Umaru Musa Yar’adua University, Katsina, to study the occurrence of aflatoxins in packaged and unpackaged powdered milk samples using Thin Layer Chromatography (TLC) and to isolate and identify the associated fungal species. Aflatoxin contamination of powdered milk poses a significant health risk, particularly in regions where monitoring and quality control are insufficient. This study aimed to isolate and characterize aflatoxins in packaged and unpackaged powdered milk samples collected from selected vendors in Katsina State. The extracts exhibited variability in texture, predominantly watery with oil suspensions, whereas a smaller subset showed an oily appearance. Aflatoxin G was detected in both packaged and unpackaged powdered milk samples, with blue-green fluorescence observed in samples P2, P3, P5, P6, P7, P10, U1, U4, U6, and U7. Aflatoxin B was identified in samples P8, U2, U3, U8, U9, and U10, which exhibited characteristic blue fluorescence under UV light. Morphological analysis of fungal isolates revealed a predominance of Aspergillus niger and Aspergillus flavus, both characterized by non-branched conidiophores with bulbous ends and conidia arranged in a sunbeam pattern. Notably, A. Niger was primarily associated with packaged milk samples, whereas A. flavus was frequently detected in unpackaged samples. These findings highlight the health risks associated with aflatoxin contamination in powdered milk and underscore the urgent need for enhanced regulatory oversight. Strengthening surveillance systems, enforcing stringent quality control standards for both packaged and unpackaged dairy products, and aligning local food safety protocols with international standards are critical for protecting consumer health in Katsina State and beyond.